lncRNA differentiation antagonizing nonprotein coding RNA overexpression accelerates progression and indicates poor prognosis in pancreatic ductal adenocarcinoma - Chen, Lei (Onco Targets Ther, 2018)
BACKGROUND: lncRNA differentiation antagonizing nonprotein coding RNA (lncRNA DANCR) has been suggested to play an oncogenic role in multiple cancers. However, to the best of our knowledge, the clinical significance and role of DANCR in pancreatic ductal adenocarcinoma (PDAC) has not been illuminated till now. The present study aims to identify the functional role of DANCR in PDAC. METHODS: The expression of DANCR was detected in PDAC cells and tissues. The correlation of DANCR expression and PDAC clinicopahological features was analysed. Kaplan-Meier method was used to depict the overall survival (OS) rate and shorter progression-free survival (PFS) of PDAC patients, and Log-rank test was performed to analyse the difference. Univariate and multivariate COX regression model were utilized to analyse the risk factors for prognosis. Transwell assay and Matrigel assay were conducted to detect the effect of DANCR on the migration and invasion of PDAC cells, respectively. Colony formation assay and Cell Counting Kit-8 (CCK-8) assay were performed to evaluate the function of DANCR on proliferation. The mechanisms of DANCR exerting its function were also explored. RESULTS: DANCR was revealed to promote PDAC progression, with relatively higher expression levels in PDAC cell lines and tissues. Correlation analysis of the clinicopathological features and DANCR expression found that high DANCR expression was statistically correlated with vascular invasion (P=0.013), advanced T stage (P=0.005), lymph node metastasis (P<0.001) and advanced TNM stage (P<0.001). Notably, survival analysis discovered that high DANCR expression predicted lower OS rate and shorter PFS period. In addition, high DANCR expression was identified as an independent risk factor for poor OS (HR=1.199, 95% CI=1.113–1.290, P<0.001) and PFS (HR=1.199, 95% CI=1.114–1.290, P<0.001) of PDAC. Moreover, in vitro assays detected that the migration and invasion of Panc1 cells with DANCR deficiency were significantly suppressed in the Transwell assay and the Matrigel assay. However, the motility of BxPC3 cells with DANCR overexpression was obviously increased. In addition, the loss of DANCR suppressed the proliferation of Panc1 cells in the CCK-8 assay and the colony formation assay, while ectopic expression of DANCR in BxPC3 cells promoted the proliferation. Besides, microRNA-33a-5p/AXL signaling pathway may be involved in mediating the function of DANCR. CONCLUSION: Overexpression of lncRNA DANCR in PDAC is associated with cancer progression and predicts poor OS and PFS. DANCR could promote the proliferation and metastasis of PDAC cells. DANCR may serve as a potential prognostic marker and therapeutic target in PDAC.